Ghosts as Guests Psychic Visits Spirits who Linger at Hotel - Nathanson, Rick (Albuq. Journal Albuquerque, NM, 1989)
This article is about Psychic Jacque Littlejohn Cooley visiting the St. James Hotel and talking with its ghosts.
Newspaper article + Photographs 1)Crystal Ball 2) Chain-smoking psychic 3)Jacque Littlejohn Cooley
Mater List Item # 12
File location is in the New Mexico File Cabinets
Keywords: Cooley, Jacque Littlejohn; Wright, Jesse (James); Sitzberger, Ed; Sitzberger, Pat; Wright, T. J; Woody the Imp; Lambert, Mary; Lambert, Henri; Griego, Pancho; Allison, Clay; Masterson, Bat; Earp, Wyatt; St. James Hotel; Paranormal Investigations; Psychics; Psychic Walk Through; Business History; Card Games; Fights; Ghosts; Haunted Hotels; Psychic Readings; Cimarron, New Mexico